THE MEANING OF ALPHA FEMALE IN FEMALE LIBRARIAN: Building a Positive Image of Libraries through Female Librarians as Alpha Female - Yunus Winoto; Tine Silvana Rachmawati (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
MAKNA DIRI ALPHA FEMALE PADA PUSTAKAWAN PEREMPUAN:Membangun Citra Positif Perpustakaan Melalui Kiprah Pustakawan Perempuan Sebagai Alpha FemaleAbstractThe profession of librarians is often associated with women. This can be justified if we refer to data and research results that have been done in several countries. However, many women who work in the library, this does not necessarily describe that library work is a simple and easy job. However, on the contrary, work in the field of library is increasingly complex and demands the competence and mastery of information technology. Moreover, the expectations of some users who demand a fast and quality service. Therefore to answer this problem required a female librarian who has the competence, intelligent and able to become a leader for his group and can show the characteristics as a professional. As for the description of people like this people call it with the term alpha female. With the birth of alpha female figures among female librarians is expected to change the positive image of librarians and library institutions. This is because the female alpha figure in the female librarian is a figure of women who are considered "perfect" are still rare today.Keywords: library, librarian, symbolic interaction, alpha female. AbstrakProfesi pustakawan kerapkali dikaitkan dengan kaum perempuan. Hal ini dapat dibenarkan jika kita merujuk pada data dan hasil riset yang telah dilakukan di beberapa negara. Namun demikian banyaknya kaum perempuan yang bekerja di perpustakaan, ini tidak serta merta menggambarkan bahwa pekerjaaan perpustakaan merupakan pekerjaan yang sederhana dan mudah.  Namun justru sebaliknya pekerjaaan di bidang perpustakaan saat ini semakin kompleks dan menuntut kompetensi dan penguasaan teknologi informasi. Apalagi harapan sebagian pengguna yang menuntut suatu pelayanan ayang cepat dan berkualitas. Oleh karena demikian untuk menjawab permasalahan ini diperlukan sosok pustakawan perempuan yang memiliki kompetensi, cerdas serta mampu menjadi pemimpin bagi kelompoknya dan bisa menunjukkan ciri-ciri sebagai seorang profesional. Adapun gambaran orang seperti ini orang menyebutnya dengan istilah alpha female. Dengan lahirnya sosok alpha female di kalangan pustakawan perempuan diharapkan mampu merubah citra yang positif terhadap pustakawan dan lembaga perpustakaan. Hal ini dikarenakan sosok alpha female pada diri pustakawan perempuan  merupakan sosok wanita yang dianggap “sempurna” yang masih jarang ditemukan saat ini.Kata Kunci : perpustakaan,  pustakawan, interaksi simbolik,  alpha female.